2019
DOI: 10.21608/mjcu.2019.80706
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasound in Assessment of Menisco-Ligamentous Injuries of Knee Joint in Comparison with Magnetic Resonance Imaging

Abstract: Background: While considering the Magnetic Resonance Imaging (MRI) as 'gold standard' for detection of knee ligamentous and meniscal injuries, we are determining the usefulness of Ultrasound (US) in various knee injuries and correlate the findings of US with the findings of MRI.Aim of Study: to assess the diagnostic utility of ultrasound in patient with suspected ligaments or menisci injuries of knee joint keeping MRI as the Gold standard.Material and Methods: This prospective study included 30 patients who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Those between the ages of 24 and 34 made up the largest demographic, while men made up 75% of the total. Moreover, Marwa et al (10) examined Thirty individuals who had been diagnosed with a possible knee ligament or meniscal tear. Those between the ages of 18 and 57 made up the bulk of the patients, with men being 70percent of the total and women making up 30%.…”
Section: Mohanan and Unnikrishnanmentioning
confidence: 99%
See 1 more Smart Citation
“…Those between the ages of 24 and 34 made up the largest demographic, while men made up 75% of the total. Moreover, Marwa et al (10) examined Thirty individuals who had been diagnosed with a possible knee ligament or meniscal tear. Those between the ages of 18 and 57 made up the bulk of the patients, with men being 70percent of the total and women making up 30%.…”
Section: Mohanan and Unnikrishnanmentioning
confidence: 99%
“…Furthermore, Cook et al (12) showed that US and MRI of meniscus pathology had similar levels of sensitivity (91.2 % vs. 91.7 %), specificity (84.2% vs. 66.7%), positive predictive value (PPV) (94.5% vs. 84.6%), negative predictive value (NPV) (76.2% vs. 80%), and overall accuracy (89.5% vs. 81.1%). Moreover, Marwa et al (10) found that 15 instances (50%) were identified with U/S as having a posterior horn of medial meniscus damage, whereas 18 cases (60%) were diagnosed with MRI. In spite of this, posterior horn of lateral meniscus damage was identified in both Ultrasound and MRI in 5 patients (16.7%).…”
Section: Mohanan and Unnikrishnanmentioning
confidence: 99%